Pengaruh Influencer Marketing terhadap Keputusan Pembelian Baso Aci Akang Bandung, Indonesia - Isna Amelia Nurhamidah (International Journal Administration, Business & Organization, 2022)
The purpose of this study is to determine whether there is an influence from influencer marketing on consumer purchasing decisions for Baso Aci Akang Bandung and to find out how big the influence is. The study used a descriptive survey method, namely the research was conducted by distributing questionnaires through the g-form to the respondents. Respondents amounted to 100 people and had purchased meatballs from Bandung. Data processing was carried out using the normality test, linearity test and simple linear regression analysis. The results obtained indicate that influencer marketing has a positive and significant influence of 43.8% on purchasing decisions at Baso Aci Akang Bandung. This value is known by looking at the R Square column or the coefficient of determination in the table of simple linear regression analysis results. In addition, there is a strong correlation between the two variables. From the results of simple regression analysis obtained a correlation coefficient that can be seen from table R with a magnitude of 0.662. This value shows the relationship between influencer marketing and purchasing decisions is included in the strong category because it is in the range 0.41 – 0.70.